ANALISIS POTENSI LONGSOR LERENG BUKIT TUI KELURAHAN TANAH HITAM KOTA PADANG PANJANG SUMATERA BARAT MENGGUNAKAN APLIKASI SLIDE V6.0 - Yoszi Mingsi Anaperta; Septian Andika Putra (Jurnal Teknologi Informasi dan Pendidikan, 2019)
Tui Hill is a limestone hill lined south of Padang Panjang. It is located between Rao-Rao Village and Tanah Hitam. Based on the results of investigations of researchers on the slopes of Bukit Tui limestone in the coordinates S0 ° 28'21.3 "E100 ° 24'00.4ʺ which are in the Tanah Hitam Village, there are many weak fields such as burly, steep slope geometry, influence on earthquake vibrations, and rainfall the high can lead to landslides on slopes, potential for landslides on the slopes of research can endanger road users and community settlements on slope locations. This study aims to analyze the potential of landslides based on the physical and mechanical properties of intact rocks, using the boundary equilibrium method. Then make reinforcement recommendations so that slope conditions are safe / stable. Based on the results of analysis and calculations in saturated conditions with the influence of earthquake factors 0,7 - 0,9g the values ​​of FK 1,461, 1,295, and 1,144 were obtained. From the results of the analysis, the slope is unsafe / unstable. In the original condition with 0.9g earthquake factor, FK 1.364 is obtained. Based on the results of analysis and calculations, the slope reinforcement recommendation used is the wire mesh installation method (wiremesh) in slope face.